Implementasi Program Pemberian Beasiswa Daerah Untuk Mahasiswa Kabupaten Lamandau - Yullya Putri Utami (Journal Ilmu Sosial, Politik dan Pemerintahan, 2021)
The implementation of public policy is one of the activities in a public policy process that determines whether a policy is in contact with the public interest and can be accepted by the public. Implementation of the Regional Scholarship Program for Lamandau Regency Students based on the Regulations of the Regent of Lamandau Number. 24 of 2013. The scholarship program in the Lamandau Regency area has been in place since 2009 and this program was carried out by the Education and Culture Office of Lamndau Regency. This program aims to help students from Lamandau Regency to accelerate the lecture process and to improve human resources. This study uses a qualitative approach, data collection obtained from interviews, observation, and documentation. And using data analysis techniques in the form of data reduction, data presentation and conclusion drawing. In this study the author uses the Geogre C. Edward III policy implementation model with 4 (four) variables, namely communication, resources, position and bureaucratic structure. Based on the results of the research based on communication variables, it is still not optimal. The lack of socialization from the Dinas to students who will receive scholarship assistance, for resources such as the number of staff, facilities and infrastructure is sufficient. As for the inhibiting factors for this program, the delay in channeling funds from the company as donors and students is still lacking pay attention to systematics, and the requirements set by the Education and Culture Office of Lamandau Regency.